Legal Consequences of Concealing Adopted Children's Lineage: A Comparative Study Between Indonesian Criminal Law and Islamic Law on Identity, Inheritance, and Child Protection - Ahmad Nizar Mohammad Syamwil; Maulidya Mora Matondang; Ramadhan Syahmedi Siregar; Akmaluddin Syahputra (Jurnal Sahabat ISNU SU, 2026)
Concealing the ancestry of adopted children constitutes a complex legal issue that involves the intersection between criminal law, child protection, and Islamic legal principles. Adoption in contemporary society is no longer merely a social relationship of care but also generates significant legal consequences concerning personal identity, lineage, inheritance rights, guardianship, and family relations. In Indonesia, the legal framework of adoption reflects a pluralistic character, where national law prioritizes the protection of children’s rights and administrative certainty, while Islamic law strictly maintains the preservation of nasab (lineage) as an essential element of individual legal status. The practice of concealing the biological origins of adopted children creates a conflict between social perceptions that often place adopted children in an equivalent position to biological children and legal principles requiring transparency of identity. This study aims to examine the legal consequences of concealing the ancestry of adopted children from the perspectives of Indonesian criminal law and Islamic law. This research employs a normative juridical method using statutory and conceptual approaches through analysis of relevant legislation, the Compilation of Islamic Law, and Islamic legal doctrines. The findings indicate that concealing the ancestry of adopted children may constitute a legally prohibited act under Indonesian criminal law, particularly when accompanied by false statements, unlawful adoption procedures, or manipulation of a child’s identity, which may result in criminal liability. From the perspective of Islamic law, such concealment contradicts the principle of maintaining nasab and may create legal consequences concerning inheritance, marriage guardianship, and familial status. Islamic law permits adoption in the form of kafalah, emphasizing protection and care without altering the child’s original lineage. This study concludes that transparency regarding the origins of adopted children is a fundamental legal obligation that serves to protect children’s rights, prevent future legal disputes, and harmonize positive law with Islamic legal values in Indonesia’s adoption system.